Analysis of Factors Influencing Purchasing Decisions on Shopee E-Commerce - Hardianawati; Sundari Soekotjo; Dwi Novita Sari; Prasastiara Eka Marsella (Jurnal Multidisiplin Madani, 2024)
The aim of this research is to ascertain and evaluate the relative and concurrent impact of pricing, discount, and cashback on people's decisions to buy on e-commerce sites like Shopee. This study used a quantitative methodology, with 100 samples of Shopee e-commerce consumers from the community of Jl.Kp.Beting Jaya Rt.08/18 as the population. The dissemination of the Google Form questionnaire and a literature review are used in the data collection procedure. The author employs the Nonprobability Sampling Method, specifically the Convenience and Snowball sampling techniques, for sampling. The validity test, reliability test, hypothesis test, determination coefficient test, multiple linear regression analysis, F test, and test are the analyses that were employed in this investigation. Based on the T and F tests, the study's findings indicate that price, discount, and cashback together significantly impact e-commerce Shopee consumers' purchase decisions; the computed f value (43.210)> f table (3.091) and sig (0.001) <0.05 support this conclusion. H0 was rejected and Ha was allowed based on the computed T value of (5.720) H1 (3.844) H2 (3.629) H3 > t table (1.985) and sig 0.001 < 0.05